The participation of women and children in Latin American and Caribbean agriculture - Herpen, D. van (International Center for Tropical Agriculture, 1991)
This paper reviews the literature on the participation of women and children in agricultural activities in Latin America and the Caribbean. The review focuses on participation through labor in agriculture overall and in certain agricultural activities in particular. Also reviewed are the rural family`s access to and capacity for decision-making on resources. Factors influencing such participation are analyzed, such as farm size, land ownership, income levels, racial origin, and destiny of production. A hypothesis proposes that agriculture within this region is becoming increasingly dominated by women. The implications this phenomenon would have for the design and transfer of agricultural technology are analyzed. The significant role played by women and children in food production is demonstrated and the importance of involving them in the development of agricultural technology in order to guarantee its adoption is highlighted. It is proposed that the gender variable should become an integral part of CIATs research. Case studies on CIAT cornmodities--beans, cassava, rice, and tropical pastures--are included, together with statistical information.